SEASONAL INCIDENCE OF COCONUT MOTH, BATRACHEDRA ARENOSELLA WALKER (LEPIDOPTERA : BATRACHEDRIDAE) - PRASHANTHA, C.; SHIVASHANKAR, T.; GOWDA, D.K. SIDDE; JAGADISH, K.S.; VANITHA, B.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
Coconut moth, Batrachedra arenosella Walker (Lepidoptera : Batrachedridae) infestation was proved to be one of the major factors responsible for immature nut fall in coconut ecosystem in South India. The larvae feed on the mesocarp of immature nuts under the perianth forming a silken web with excretory pellets. Its infestation predisposes the nuts to secondary infection by other pests and micro organisms. Feeding by B. arenosella larvae near the stalk of the nut leads to premature nut fall. Therefore investigations on the seasonal incidence of were undertaken at V.C. Farm, Mandya during 2011-12. Its incidence was more abundant on coconut during August. Adults were active throughout the year as evidenced by moth catches in all the months. The trap catches of B. arenosella exhibited a negative association with weather parameters viz., maximum temperature, sunshine hours, rainfall and positive relation with minimum temperature, morning relative humidity and afternoon relative humidity. The trap catches were found to be significantly positively correlated with wind speed. Nut damage by the larvae exhibited a negative association with maximum temperature, sunshine hours and rainfall. The incidence of the larvae was observed in the intact nuts throughout the year. An average of 11.82% incidence was observed on intact nuts which accounts for 22.39% of fallen nuts. A positive association was observed between adult trap catches and field incidence of B. arenosella on the immature nuts.